From Nollywood to the World: A Cultural Studies and Critical Discourse Analysis of Nollywood Films on Netflix - Afolabi, Ololade (International Journal of Mass Communication, 2024)
This study examines the transnationalization of the Nollywood industry in the rise of streaming platforms like Netflix. As nonwestern film industries begin to find global audiences beyond their local space, ideological underpinnings of these industries also continue to shift and become more apparent. The need to compete for global capital while retaining the cultural flavor of the South has been a major challenge of many transnational media industries. Taking Nollywood as a case study, this study argues that the production of Nollywood films on Netflix goes beyond the quest to find global market, instead economic interest, the need to appeal to global audience by producing multicultural relevant content and promulgating a Nigerian identity that non-African audience can understand are important areas that should be considered. Contextualized within the theories of cultural studies and political economy and the method of critical discourse analysis, the study accentuates the changing discourse of the new Nollywood cinema and what it means for critical cultural scholarship of media and communication, especially in the Global South.